P-174 'Help me be the best that i can be'. a bespoke specialist palliative care experience for student nurses. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Gibson, Vanessa; Nicol, Jane
Abstract : Bridging the practice and theory gap within specialist palliative care is hugely important if we are to ensure that all patients, in all settings have access to skilled, compassionate care. Student nurses within South Worcestershire were increasingly highlighting a lack of confidence and exposure to palliative care. Comments of final year student nurses included: 'I would like to have exposure to palliative care for the first time during my training rather than when I am qualified' Traditional ad hoc placements appeared to be failing to meet growing student demands. As a result the community nursing services led the development of a comprehensive bespoke multidisciplinary educational opportunity. From an initial suggestion that with more planning and time we could have a significant impact upon the nurses of the future the project has evolved to include: An on line preparatory workbook A full education day within a hospice setting, giving the students the opportunity to observe a mock MDT, set their learning agenda, meet specialist multidisciplinary staff and see clinical departments An opportunity for students to choose a minimum of one day clinical placement within the hospice multidisciplinary teams. This includes chaplaincy, medical staff, inpatient unit, Clinical Nurse Specialists, Counselling and Hospice at Home Clear outstanding learning needs identified for clinical placements A student led second educational day which sees students apply learning gained to case studies, identify any outstanding learning needs and explore self-care techniques. This opportunity is offered to all student branches at an appropriate point within training. Close work with University staff has been essential to the success of this project. Evaluations from student participants have been extremely positive, examples include: 'One of many favourite days of my whole training and I am very thankful for the opportunity' We feel this project is comprehensive and transferable. We are currently exploring a similar opportunity for registered nurses.